Mask and shame of ageing - Barański, Jarosław (Hybris, 2016)
The concept of ageing as a mask refers to, according to M. Featherstone and M. Hepworth, the tension between the identity and experiencing one’s own, aging body. There is a growing disparity between the body and “ I" in the elderly, which results from the fact that they lose “ symbolic capital" and do not accept their own bodies with their mental and physical limitations. Old age exposes and becomes a symbolic nudity, a source of shame in the culture full of images of beautiful, young, physically fit and sexually attractive bodies. We compensate shame and the loss of the symbolic vestment by rejuvenating our bodies and suppressing negative emotions. Old age has become painful, because people live longer than ever before. To justify all treatments aimed at prolonging life, contemporary culture has taken for granted the idea of Hufelad from 1897: “ Long life has always been the main desire and goal of humanity" [1905, 6]. Now, when we embark on prolonging life, we face the problems of recognizing the sense of identity and its social expression in the process of extended ageing, the relationship between our identity and our aging body, which is still an existential project.